Adolescent Fathers with Unplanned Pregnancies and Their Journey in English as a Second Language Learning: a Multiple Case Study - Obenza, Brandon; Suerte, Josephine M.; Raymunde Jr., Pedro P; Sumayo, Gideon S. (Journal of Educational, Health and Community Psychology, 2025)
Adolescent fatherhood, particularly in the context of unplanned pregnancies, presents unique challenges that disrupt educational and linguistic development. This study explored the lived experiences, challenges, and coping mechanisms of young fathers in relation to learning English as a second language. Using a qualitative multiple case study design, five adolescent fathers from public and alternative learning institutions in Mindanao, Philippines, were purposively selected. Data were gathered through semi-structured interviews, classroom observations, and document analysis, then analyzed using Colaizzi’s thematic method with member checking and triangulation to ensure rigor. Findings revealed struggles with English proficiency, comprehension difficulties, and emotional strain, but also highlighted persistence, child-driven motivation, and adaptive time management as coping strategies. The study extends Role Conflict Theory, Self-Determination Theory, and Ecological Systems Theory by illuminating how adolescent fathers negotiate competing roles. Practical implications include designing flexible class schedules, providing targeted ESL tutoring, and implementing school- and community-based support programs for young fathers.